Morbidity and Mortality of Firearm Injury at A Tertiary Care Hospital in Lahore - M. MAQSOOD, MARIAM ARIF, SYED HAMAD RASOOL (Journal of Fatima Jinnah Medical University, 2018)
Background: Throughout the world violent crimes due to firearm weapons have increased tremendously which are destabilizing political, social, and economic systems, and causing increase in morbidity and mortality. Objective: The aim of the study was to determine the pattern of firearm injuries and to assess their outcome at a tertiary care hospital in Lahore. Materials and Methods: This retrospective study was conducted in Surgical Unit- IV of Services hospital, Lahore from January2011 to December 2013. Data was collected regarding age, gender, date of incident, manner of infliction of injuries, site of external and internal injuries, number of wounds and outcome. It was tabulated and statistically analyzed on SPSS version17. Results: Total number of cases of firearm injury was 150 with male to female ratio 11.5 : 1. Commonest age group affected was third decade(52, 34.6%). The most commmonly involved body region was abdomen (54, 36%). The incidence of homicidal cases was 99% while that of accidental was 1% . No suicidal cases were reported. 56% sustained internal injuries with small bowel (50.9%) and liver (16.9%) most frequently injured in abdomen and lungs (71.4%) extra abdominally. The overall mortality rate was 5.3%. Conclusion: Firearms and their use are modifiable risk factors which if recognized and addressed can significantly reduce the firearm related morbidity and mortality in the country.